ASSESSMENT OF CORPORATE CULTURE OF INTERNATIONAL COMPANIES BY A MODEL OF THE CRANDFIELD BUSINESS SCHOOL - Svetlana M. Maksimova (Статистика и экономика)
The article presents a model of corporate culture of the Сrandfield Business School and describes its components. This model is used as a basis for the analysis of the corporate culture of large companies in Germany, Japan and Russia. The study revealed similarities and differences in corporate cultures of companies from different countries, considered and described the national characteristics of the corporate culture of the main components of the model of the Сrandfield Business School.